Предмет: Алгебра,
автор: Polinaaaaaas
упростить выражение *корень*(8-*корень*11)*квадрат*+*корень*(3-*корень*11)*квадрат*
Ответы
Автор ответа:
0
sqrt(8-sqrt(11))=I8-sqrt(11)I=8-sqrt(11), 8-sqrt(11)>0
sqrt(3-sqrt(11))=I3-sqrt(11)I=sqrt(11)-3, 3-sqrt(11)<0
8-sqrt(11)+sqrt(11)-3=5
I8-sqrt(11)I абсолютная величина
Похожие вопросы
Предмет: Алгебра,
автор: kot1200000
Предмет: Биология,
автор: 889miroxa889
Предмет: Английский язык,
автор: shahinatojimurodova
Предмет: Геометрия,
автор: maruca
Предмет: Обществознание,
автор: ybrbnf145